Understanding Broken Communication: Parent-Child Relationships in Broken Home Families - Meidelina, Alya Verda; Rahmah, Jasmine Aulia; Siswoyo, Mukarto (Pelopor Publikasi Akademika, 2025)
This research focuses on understanding the factors contributing to misunderstandings in family communication, particularly within broken home families. A broken home refers to families experiencing disharmony or separation due to various factors, such as emotional conflicts, financial stress, or external pressures. The aim of this study is to explore these factors in-depth and provide practical solutions for improving interactions between parents and children in these families. Using a descriptive qualitative research method, the study analyzes communication patterns in dysfunctional families, providing a detailed understanding of the underlying issues. The findings reveal that openness in communication is crucial for rebuilding healthy parent-child relationships. Effective communication not only plays a key role in conflict resolution but also lays the foundation for creating a harmonious family environment based on understanding, trust, and mutual support. This research highlights the importance of nurturing family communication skills to strengthen family bonds and offers insights into how families can foster more positive and supportive relationships.